An unusual endodontic complication following crown lengthening surgery: A Case Report - Tong Wah Lim; Teng Kai Ong (Universidad de Concepción., 2021)
A gummy smile is a form of excessive gingival display when smiling. The excessive gingival display due to altered eruption is likely to benefit from crown lengthening surgery in order to restore the esthetic smile. Case Report: The potential complications of the crown lengthening surgery include possible esthetic deformities, dentine hypersensitivity, transient mobility, and root resorption. The present case report reveals a rare complication happened after an esthetic crown lengthening surgery which was performed to correct the gummy smile of a 37-year-old female. The patient experienced dull throbbing pain and mild tender to percussion on tooth 11, 3 weeks after the surgery, and the symptoms did not improve after the composite restorations were placed at the cervical regions. Instead, the tooth was tender to percussion and palpation with a sign of coronal discoloration. Pulp necrosis was confirmed with the clinical tests. A cone-beam computed tomography was taken after the root canal treatment, and apical fenestration on tooth 11 was noted. Therefore, this case report shows the possible correlation between crown lengthening surgery on a tooth with apical fenestration and pulp necrosis, if the apical vasculature is severed accidentally during the procedure. Conclusion: A cone-beam computed tomography should be considered prior to the surgery and extra precaution during the surgery may reduce the risk of severing the apical vasculature if apical fenestration is evidenced.